Essays in Behavioral Personnel Economics - Reggiani, Tommaso <1983> (Alma Mater Studiorum - Università di Bologna, 2012)
The thesis contemplates 4 papers and its main goal is to provide evidence on the prominent impact that behavioral analysis can play into the personnel economics domain.The research tool prevalently used in the thesis is the experimental analysis.The first paper provide laboratory evidence on how the standard screening model–based on the assumption that the pecuniary dimension represents the main workers’choice variable–fails when intrinsic motivation is introduced into the analysis.The second paper explores workers’ behavioral reactions when dealing with supervisors that may incur in errors in the assessment of their job performance.In particular,deserving agents that have exerted high effort may not be rewarded(Type-I errors)and undeserving agents that have exerted low effort may be rewarded(Type-II errors).Although a standard neoclassical model predicts both errors to be equally detrimental for effort provision,this prediction fails when tested through a laboratory experiment.Findings from this study suggest how failing to reward deserving agents is significantly more detrimental than rewarding undeserving agents.The third paper investigates the performance of two antithetic non-monetary incentive schemes on schooling achievement.The study is conducted through a field experiment.Students randomized to the main treatments have been incentivized to cooperate or to compete in order to earn additional exam points.Consistently with the theoretical model proposed in the paper,the level of effort in the competitive scheme proved to be higher than in the cooperative setting.Interestingly however,this result is characterized by a strong gender effect.The fourth paper exploits a natural experiment setting generated by the credit crunch occurred in the UK in the2007.The economic turmoil has negatively influenced the private sector,while public sector employees have not been directly hit by the crisis.This shock–through the rise of the unemployment rate and the increasing labor market uncertainty–has generated an exogenous variation in the opportunity cost of maternity leave in private sector labor force.This paper identifies the different responses.